2017
DOI: 10.1136/bmjopen-2016-012926
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profiles of the cross-sectional and prospective participant groups in the second Diabetes MILES—Australia (MILES-2) study

Abstract: PurposeMore research into the psychosocial aspects of diabetes is needed so that the health and quality of life of people with the condition can be improved. To fill this gap, we conducted the second Diabetes MILES—Australia study (MILES-2), a survey focused on psychological, behavioural and social aspects of diabetes. The aim of the MILES-2 study was to provide a (1) longitudinal follow-up of the original MILES 2011 study cohort; (2) cross-sectional assessment of a new cohort.ParticipantsEligible participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 81 publications
2
36
0
Order By: Relevance
“…This study uses cross‐sectional data from the second Diabetes MILES–Australia (MILES‐2) study, a national online survey focused on the psychosocial aspects of living with diabetes. The methods and overall sample characteristics have been published elsewhere .…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses cross‐sectional data from the second Diabetes MILES–Australia (MILES‐2) study, a national online survey focused on the psychosocial aspects of living with diabetes. The methods and overall sample characteristics have been published elsewhere .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Potential participants were directed to the study website to provide informed consent, be screened for eligibility and access the online survey. The total MILES‐2 sample includes 2342 English‐speaking Australians with Type 1 or Type 2 diabetes, aged 18–75 years . The current study includes participants with insulin‐treated Type 2 diabetes (531, 23%), and excludes participants using insulin pump therapy ( n = 2) or with missing data on the Insulin Treatment Appraisal Scale (ITAS; n = 73).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Although this study has several strengths (noted above and reported elsewhere) [12], some limitations must be acknowledged. First, because the data are cross-sectional it is not possible to make any causal inferences, although it should be noted that the theoretical background linking prospective memory performance to medication forgetting is robust.…”
Section: Discussionmentioning
confidence: 94%
“…The MILES-2 study included a wide range of self-report measures, which have been described in detail elsewhere [12]. Measures relevant to the current study are described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation